2022
DOI: 10.3390/cancers14040920
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Endocrine Therapy on Cognitive Function in Patients with Breast Cancer: A Comprehensive Review

Abstract: Endocrine therapy forms the backbone of systemic therapy for the majority of persons with early and late-stage breast cancer. However, the side effects can negatively affect quality of life, and impact treatment adherence and overall oncological outcomes. Adverse effects on cognition are common, underreported and challenging to manage. We aim to describe the nature, incidence, risk factors and underlying mechanisms of endocrine therapy-induced cognitive dysfunction. We conducted a comprehensive literature revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 88 publications
1
16
0
Order By: Relevance
“…Approximately two‐thirds of BC cases are postmenopausal at diagnosis and over 80% receive endocrine therapy (ET) 2 . CRCD is associated with ET in women with BC, 3 and compromises psychological well‐being, occupational achievement, decision making, self‐management, and cancer therapy adherence 4 . We previously reported that, compared to matched controls, postmenopausal women with BC receiving aromatase inhibitor (AI) therapy demonstrated poorer executive function at pre‐therapy that persists through the first 18 months of therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately two‐thirds of BC cases are postmenopausal at diagnosis and over 80% receive endocrine therapy (ET) 2 . CRCD is associated with ET in women with BC, 3 and compromises psychological well‐being, occupational achievement, decision making, self‐management, and cancer therapy adherence 4 . We previously reported that, compared to matched controls, postmenopausal women with BC receiving aromatase inhibitor (AI) therapy demonstrated poorer executive function at pre‐therapy that persists through the first 18 months of therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Endocrine therapies have been shown to increase both subjective cognitive complaints and objective cognitive testing 85. Current evidence shows that the deleterious effects of endocrine therapies may predominantly affect verbal memory and processing speed, rather than global cognitive deficits 86. Several studies suggest that verbal memory is mostly affected in endocrine therapies 87.…”
Section: Putative Mechanisms Of Endocrine Therapy Induced Cognitive I...mentioning
confidence: 99%
“…Advances in cancer detection and treatment have increased the average five-year survival rate for breast cancer patients to 90% 1 . Endocrine therapy (ET) such as tamoxifen and/or aromatase inhibitors reduces the risk of breast cancer recurrence in patients with estrogen receptor positive tumors (60% of breast cancer) 2 , but is often accompanied by complaints of cognitive impairment (independent of chemotherapy) 3 5 . Endocrine therapy-induced adverse effects on cognition are common, clinically underreported, and challenging to manage.…”
Section: Introductionmentioning
confidence: 99%